Charles N. Elliot collection - Elliot, Charles N. (Charles Nathan), 1873-
Correspondence relating to research on Walt Whitman, to the collection and preservation of Whitman artifacts and manuscripts, and to personal and family affairs; a small collection of Walt Whitman manuscripts; printed matter; and miscellaneous items. Includes trial lines and a draft of the poem titled, "Nay, Tell Me Not To-day the Published Shame," published March 5, 1873. Elliot's correspondents include Alfred Bishop Beers, Richard Maurice Bucke, Margaret Wade Campbell Deland, Ward Hampton Edwards, John Erskine, Henry Scholey Saunders, Edwin Seaborn, Daniel Edward Sickles, Harriet Appleton Sprague, and Anne Montgomerie Traubel. Also includes letters between Richard M. Bucke and William Douglas O'Connor.
In part, transcripts.
Collector and researcher of Walt Whitman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beers, Alfred Bishop, -- 1845-1920 -- Correspondence; Bucke, Richard Maurice, -- 1837-1902 -- Correspondence; Deland, Margaret Wade Campbell, -- 1857-1945 -- Correspondence; Edwards, Ward Hampton, -- 1878- -- Correspondence; Erskine, John, -- 1879-1951 -- Correspondence; O'Connor, William Douglas, -- 1832-1889 -- Correspondence; Saunders, Henry Scholey, -- 1864-1951 -- Correspondence; Seaborn, Edwin, -- 1872- -- Correspondence; Sickles, Daniel Edgar, -- 1825-1914 -- Correspondence; Sprague, Harriet Appleton -- Correspondence; Traubel, Anne Montgomerie, -- 1864-1954 -- Correspondence; Whitman, Walt, -- 1819-1892.; Collectors; Researchers